E-062 True aneurysms of the posterior communicating artery: a systematic review and meta-analysis of individual patient data. (16th November 2010) - He, W; Gandhi, C; Quinn, J; Karimi, R; Catrambone, J; Prestigiacomo, C
Abstract : Introduction: The term 'true' posterior communicating artery (PCoA) aneurysm refers to an aneurysm that originates from the posterior communicating artery itself. Over the past decades, an increasing number of this type of posterior communicating artery aneurysms have been reported. We systematically reviewed all of these published data and conducted a meta-analysis on these individual patient data. Method: A meta-analysis of individual patient data was conducted. Results: Pooled data demonstrated that 'true' PCoA aneurysms represented about 1.3% (95% CI 0.8% to 1.7%) of all intracranial aneurysms and 6.8% (95% CI 4.3% to 9.2%) of all PCoA aneurysms. Mean age was 53.5 (53.5±15.4) years and ranged between 23 and 79 years. 49 of these reported aneurysms had the ruptured status, 44 (89.8%) were reported as ruptured and four (10.2%) were reported as unruptured. There were no significant differences in ruptured status between age (p=0.321), aneurysm side (p=0.537) and shape (p=0.408). No significant differences in complication rates were found between the different ruptured status (p=0.27) or operative modalities (p=0.878). Mean ages of those patients who had no complications and those who had complications were 53 (53±2.59) versus 53.2 (53.2±5.02) years (p =0.972). Conclusion: We concluded that 'true' PCoA aneurysms represent about 1.3% of all intracranial aneurysms and 6.8% of all posterior communicating artery aneurysms. 'True' PCoA aneurysms are more prone to rupture compared with their counterpart junctional aneurysms. When surgical management is indicated, care should be taken in choosing the operative approach to avoid oculomotor nerve damage and to preserve perforating branches as much as possible. A good understanding of the location and configuration of the aneurysm neck before surgical treatment is critical in successful treatment of these lesions.